Molecular dynamics simulations of G-DNA and perspectives on the simulation of nucleic acid structures - Sponer, Jiří; Cang, Xiaohui; Cheatham, Thomas E (Methods, 2012)
The article reviews the application of biomolecular simulation methods to understand the structure, dynamics and interactions of nucleic acids with a focus on explicit solvent molecular dynamics simulations of guanine quadruplex (G-DNA and G-RNA) molecules. While primarily dealing with these exciting and highly relevant four-stranded systems, where recent and past simulations have provided several interesting results and novel insight into G-DNA structure, the review provides some general perspectives on the applicability of the simulation techniques to nucleic acids.
Keywords: Hydrogen Bonding; Ligands; guanin; konformace nukleové kyseliny; rozpouštědla; G-kvadruplexy; telomery; DNA; Guanine; vodíková vazba; Molecular Dynamics Simulation; G-Quadruplexes; simulace molekulární dynamiky; Telomere; Nucleic Acid Conformation; RNA; ligandy; Solvents